1979
DOI: 10.1055/s-0038-1646781
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Like and Factor X-Activator Components of Bothrops Snake Venoms

Abstract: SummaryA comparative study on the coagulant activity of snake venoms was carried out in 26 Bothrops species, using specific clotting systems for the thrombin-like and the factor X- activator activities. With only two exceptions (B. erythromelas and B. castelnaudi) all venoms showed thrombin-like activity, since they were able to clot fibrinogen directly. The absence of thrombin-like action of B. erythromelas venom is due to a fibrinogenolytic effect. Five venoms (B. atrox asper, B. bilineatus bilineatus, B. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
21

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 1 publication
5
42
0
21
Order By: Relevance
“…As desordens hemorrágicas podem ser causadas provavelmente, por degradação dos fatores de coagulação (II, VIII, X) (Nahas et al 1979, Souza et al 2000, Cominetti et al 2003 e comprometimento plaquetário (trombocitopenia).…”
Section: Achados De Necropsia E Histopatológicosunclassified
“…As desordens hemorrágicas podem ser causadas provavelmente, por degradação dos fatores de coagulação (II, VIII, X) (Nahas et al 1979, Souza et al 2000, Cominetti et al 2003 e comprometimento plaquetário (trombocitopenia).…”
Section: Achados De Necropsia E Histopatológicosunclassified
“…NAHAS et al (1979) testaram os venenos de vinte e seis espécies de serpentes, determinando para o veneno de B. alternatus três ações específicas: tipo-trombina, protrombina e ativador do Fator X.…”
Section: Discussão E Conclusõesunclassified
“…In 1992, Maruyama et al (12) complemented Nahas et al's work (8) by investigating the enzymatic properties of factor II (FII) and FX activators from B. erythromelas venom. They demonstrated that both activators are inhibited by ethylenediaminetetraacetate and 1,10-phenanthroline.…”
Section: Overview On Bothrops Erythromelas Venommentioning
confidence: 99%
“…The fi rst study on this snake dates back to 1979. Nahas et al (8) , compared the coagulating activity of 26 different Bothrops snake venoms. Using a specifi c clotting system, they showed that B. erythromelas venom presents no thrombin-like activity, because it was not able to directly clot fi brinogen.…”
Section: Overview On Bothrops Erythromelas Venommentioning
confidence: 99%